Direct evidence for the occurrence of superconductivity in the magnetic compound YFe4Al8 - Rybaltchenko, L. F.; Wyder, P.; Jansen, A. G. M.; Dmitriev, V. M.; Prentslau, N. N.; Suski, W. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2002)
For the first time we present the direct evidence for superconductivity in the ternary magnetic compound YFe4Al8 with the ThMn12 type structure found via point-contact (PC) experiments on contacts between silver needle and single-crystal YFe4Al8, revealing the distinct Andreev-reflection current. The spectra measured prove the existence of normal-superconducting interface and exhibit the triangular-like shape in a vicinity of zero-bias voltage, inferring the unconventional type of superconductivity. The derived dependences of the order parameter versus temperature D(T) and m agnetic f ield D(H) are presented. D(T) follows BCS theory, whereas D(H) do not satisfy any theoretical predictions. In some cases there exists noticeable superconductivity enhancement by a weak magnetic field. The data obtained imply the v ery inhomogeneous distribution of superconductivity over the s ample volume in spite of its single crystal structure. We assume that the reason is associated with inherent magnetic inhomogeneities of this material. The highest values for the critical temperature Tc, upper critical magnetic field Hc2, and ratio 2D(0)/kTc are 7.4 K, 5 T, and 7.2, respectively.